Algal biophotovoltaic (BPV) device for generation of bioelectricity using Synechococcus elongatus (Cyanophyta) - Ng, Fong Lee; Phang, Siew Moi; Periasamy, Vengadesh; Beardall, John; Yunus, Kamran; Fisher, Adrian C. (Springer Verlag, 2018)
The exploitation of renewable energy sources for delivering carbon neutral or carbon negative solutions has become challenging in the current era because conventional fuel sources are of finite origins. Algae are being used in the development of biophotovoltaic (BPV) platforms which are used to harvest solar energy for bioelectricity generation. Fast-growing algae have a high potential for converting CO 2 from the atmosphere into biomass and valuable products. In photosynthesis light-driven splitting of water occurs, releasing a pair of electrons and generating O 2 . The electrons can be harvested and converted to bioelectricity. In this study, algal biofilms of a tropical cyanobacterial strain Synechococcus elongatus (UMACC 105) were formed on two types of electrodes, indium tin oxide (ITO) and reduced graphene oxide (rGO), and investigated for use in the algal biophotovoltaic (BPV) device. The highest maximum power density was registered in the rGO-based BPV device (0.538 ± 0.014 mW m −2 ). This illustrates the potential of this local algal strain for use in BPV devices to generate bioelectricity in both the light and dark conditions.